Atmosphere : a love story [large type] - Reid, Taylor Jenkins (Random House Large Print Publishing, 2025)
"Joan Goodwin has been obsessed with the stars for as long as she can remember. Thoughtful and reserved, Joan is content with her life as a professor of physics and astronomy at Rice University and as aunt to her precocious niece, Frances. That is, until she comes across an advertisement seeking the first women scientists to join NASA's space shuttle program. Suddenly, Joan burns to be one of the few people to go to space. Selected from a pool of thousands of applicants in the summer of 1980, Joan begins training at Houston's Johnson Space Center, alongside an exceptional group of fellow candidates: Top Gun pilot Hank Redmond and scientist John Griffin, who are kind and easygoing even when the stakes are highest; mission specialist Lydia Danes, who has worked too hard to play nice; warmhearted Donna Fitzgerald, who is navigating her own secrets; and Vanessa Ford, the magnetic and mysterious aeronautical engineer, who can fix any engineand fly any plane. As the new astronauts become unlikely friends and prepare for their first flights, Joan finds a passion and a love she never imagined. In this new light, Joan begins to question everything she thinks she knows about her place in the observable universe. Then, in December of 1984, on mission STS-LR9, it all changes in an instant."--Provided by publisher.